Novel Mechanisms and Therapeutic Targets for Ischemic Stroke: A Focus on Gut Microbiota - Bao, Zeyu; Zhang, Zeyu; Zhou, Guoyang; Zhang, Anke; Shao, Anwen; Zhou, Feng (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke is the most common type of stroke with limited treatment options. Although the pathological mechanisms and potential therapeutic targets of ischemic stroke have been comprehensively studied, no effective therapies were translated into clinical practice. Gut microbiota is a complex and diverse dynamic metabolic ecological balance network in the body, including a large number of bacteria, archaea, and eukaryotes. The composition, quantity and distribution in gut microbiota are found to be associated with the pathogenesis of many diseases, such as individual immune abnormalities, metabolic disorders, and neurodegeneration. New insight suggests that ischemic stroke may lead to changes in the gut microbiota and the alterations of gut microbiota may determine stroke outcomes in turn. The link between gut microbiota and stroke is expected to provide new perspectives for ischemic stroke treatment. In this review, we discuss the gut microbiota alterations during ischemic stroke and gut microbiota-related stroke pathophysiology and complications. Finally, we highlight the role of the gut microbiota as a potential therapeutic target for ischemic stroke and summarize the microbiome-based treatment options that can improve the recovery of stroke patients.